2021
DOI: 10.3389/fneur.2021.734515
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Myelin Protein Zero Mutations in a Group of Chinese Patients

Abstract: Mutations in the myelin protein zero gene are responsible for the autosomal dominant Charcot-Marie-Tooth disease (CMT). We summarized the genetic and clinical features of six unrelated Chinese families and the genetic spectrum of Chinese patients with myelin protein zero (MPZ) mutations. Our study reports data from a group of Chinese patients consisting of five males and one female with the age of disease onset ranging from 16 to 55 years. The initial symptom in all the patients was the weakness of the lower l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 27 publications
(50 reference statements)
0
8
1
Order By: Relevance
“…However, some scholars have suggested that adult‐onset neuropathy does not necessarily imply that the disease will be mild [27,41]. In our study, although the average CMTNS of adult‐onset patients was lower than that of infantile‐onset patients, no statistically significant difference was observed, possibly because the sample size was insufficient; the infantile patients had a younger age at onset and relatively slower progression, whilst adult patients had an older age at onset and rapid progression [11,42]. The percentage of hearing loss in our study (5.4%) was lower than that reported by Sanmaneechai et al (20.4%) in the USA and was similar to that reported by Taniguchi et al in Japan, indicating that the occurrence of hearing loss might be less frequent in east Asia [24,29].…”
Section: Discussioncontrasting
confidence: 81%
“…However, some scholars have suggested that adult‐onset neuropathy does not necessarily imply that the disease will be mild [27,41]. In our study, although the average CMTNS of adult‐onset patients was lower than that of infantile‐onset patients, no statistically significant difference was observed, possibly because the sample size was insufficient; the infantile patients had a younger age at onset and relatively slower progression, whilst adult patients had an older age at onset and rapid progression [11,42]. The percentage of hearing loss in our study (5.4%) was lower than that reported by Sanmaneechai et al (20.4%) in the USA and was similar to that reported by Taniguchi et al in Japan, indicating that the occurrence of hearing loss might be less frequent in east Asia [24,29].…”
Section: Discussioncontrasting
confidence: 81%
“…More than 300 MPZ gene mutations have been identified as the cause of inherited peripheral neuropathy, exhibiting a wide range of phenotypes with varying severity of clinical symptoms [ 7 , 9 , 13 ]. The early-onset infantile and childhood phenotypes developmentally impair myelination, while the adult-onset phenotypes are characterized by axonal degeneration without prior demyelination [ 7 , 14 ]. Sanmaneechai and colleagues provided detailed descriptions of phenotypes of MPZ mutations from a cohort of 103 patients from 71 families with 47 different mutations [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies confirmed a heterozygous identical variant of MPZ in Exon 2.c109G>A (p.Glu37Lys) for both patients 1 and 2. Inherited in an autosomal dominant fashion, this single-nucleotide variant has a cytogenetic location on chromosome 1q23.3 [ 7 , 12 ]. The variant was deemed to be of uncertain clinical significance by the lab as it has not been reported before.…”
Section: Case Presentationmentioning
confidence: 99%
See 2 more Smart Citations